Communication Health Perspective Genderin Delivery Check up result Laboratory at Sentot Hospital Indramayu - Ahmad Samsudin (Journal of Islamic Family Law, 2026)
This study put communication health as practice social that is not neutral but influenced by norm and assumptions gender Which Work in context service medical in Sentot Hospital Indramayu.  Study This aim fot analyze difference gender in pattern communication between officer laboratory and patient, as well as the implications to justice service health. Research use method descriptive-qualitative through observation light and interview semi-structured to 5 patient Woman, 5 patient man, as well as 2 officer laboratory. Data analysis was carried out through thematic coding to pattern communication, response emotional, as well as form adjustment communication based gender. Research results show existence difference significant in style communication officer to patient based on gender. Patient Woman tend more active ask, need detailed explanation regarding mark references laboratory, and shows response emotional more tall moment accept abnormal results. On the other hand, patients man interact more short often accept information without clarification and looks hide concern against a serious diagnosis. Research This give contribution to the study gender communication in service health with confirm importance approach communication gender sensitive as part from effort realize service fair health. In practical, hospitals and institutions health need provide training communication gender- based, standards delivery result sinclusive laboratories as well as room consultations that enable informative dialogue without bia. Approach This expected capable increase quality understanding patients, reducing gap services, and strengthen principle equality in service health.